When you have an exponent divided by another exponent, you subtract the exponents (only when it has the same base)
For example:
![(x^8)/(x^3) =x^(8-3)=x^5](https://img.qammunity.org/2019/formulas/mathematics/middle-school/vx6ydyi13h4rc4t0rscc2mijf8y3jhdzk2.png)
When you have a negative exponent, you move it to the other side of the fraction to make the exponent positive
For example:
![x^(-2)=(1)/(x^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/9p1y0v1dhtc7lxyzw7mexz5bh15zfbgo7k.png)
![(1)/(x^(-5))=(x^5)/(1) = x^5](https://img.qammunity.org/2019/formulas/mathematics/middle-school/opn3cl73jbpbcbv89rdpxucov0k4ayba33.png)
![(y^(-2))/(x^(-1)) =(x^1)/(y^2) =(x)/(y^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/dwbyy299qckatxt4ld8tqrlmrj892ezb5m.png)
1.
![(10^(15))/(10^3) =10^(15-3) = 10^(12)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ewialgo1ssocnlr5r1szk8a9gikvl29m6z.png)
2.
![((-3)^4)/((-3)^(-3)) =(-3)^(4-(-3))=(-3)^(4+3) = (-3)^7](https://img.qammunity.org/2019/formulas/mathematics/middle-school/1chcpzrcdu8ps8da65t4ohqay3b7lj4uzn.png)
3.
![(8)/(8^3) =8^(1-3) = 8^(-2)=(1)/(8^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/k45mq3rdab74ukqu64i8cq0vtyu0u7alao.png)
4.
![(a^(12))/(a^2) =a^(12-2)=a^(10)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/d1gkh8zk5i1tvs4wl42jcm2y8rxs0kuz2w.png)
5.
![(m^(-2)n^(16))/(m^(4)n^2) =(m^(-2-4))(n^(16-2))=(m^(-6))(n^(14))=(n^(14))/(m^(6))](https://img.qammunity.org/2019/formulas/mathematics/middle-school/6557kxecp6dj12tj3zz282jcyilw7ottqk.png)
This is one of the ways you could have done it
6.
![(p^5q^(-10))/(p^6q^(-2)) =(p^(5-6))(q^(-10-(-2)))=(p^(-1))(q^(-8))=(1)/(p^1q^8) =(1)/(pq^8)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/7io9gpsnbnzs7m9wtcqheflabt18mxe01w.png)
7.
Divide 63 and 9
![(7x^(18))/(x^(2)) =(7)(x^(18-2))=(7)(x^(16))=7x^(16)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/xalc3v9pbkskcu9xuw28ccy2b1vxwwusgq.png)
8.
![(28r^4)/(-7r^(15)) =((28)/(-7) )(r^(4-15))=(-4)(r^(-11))=(-4)((1)/(r^(11)) )=(-4)/(r^(11))](https://img.qammunity.org/2019/formulas/mathematics/middle-school/474tkov5dxtqg2o98mq9bgnvvl576ix5mm.png)
[More information with exponents]
If you multiply an exponent directly with another exponent, you multiply the exponents together
For example:
![(x^(2))^4=x^(2(4))=x^8](https://img.qammunity.org/2019/formulas/mathematics/middle-school/1uyw6oez3xlohvjnrdq1vocvhtv71j18y9.png)
![(x^(3))^5 =x^(3(5))=x^(15)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/cvxubh0xhpyarlhqscg784ss8k1b9jc9eu.png)
If you multiply a variable with an exponent by a variable with an exponent, you add the exponents
For example:
![(x^(2)) (x^6)=x^(2+6)=x^8](https://img.qammunity.org/2019/formulas/mathematics/middle-school/2x1sen6ch7jwacrx8qu5rjlqty0c34l1mw.png)
![(x^(3))(x^1)=x^(3+1)=x^4](https://img.qammunity.org/2019/formulas/mathematics/middle-school/tsdiy42dl216r3wh6dzvr8364ddz6aqiry.png)